Anteseden Kepercayaan dan Implikasinya terhadap Perilaku Tenaga Profesional pada Wakaf Tunai - Ahadin Sadri (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2019)
The development of cash waqf in Indonesia is less encouraging, although cash waqf has entered into law since 15 years ago. Starting from this background, this research intends to investigate the public's desire, in this case professional groups, to make cash endowments. This research assumes that the desire to represent cash is due to the trustworthiness of nazhir. This study examines antecedents that cause public trust in cash waqf, so they wish to do cash waqf. The results of the study indicate that all hypotheses are proven to have a positive effect, except situational normality which has a negative effect on trust of services.